HUBUNGAN KEBIASAAN SARAPAN PAGI DENGAN STATUS GIZI DAN KONSENTRASI BELAJAR MURID DI SDN BATU TULIS KABUPATEN BOGOR TAHUN 2022 - Syasa Rahma Fadila, (2022)
As many as 16.9%-50% of school-age children in Indonesia do not usually eat breakfast, even though breakfast contributes 20-25% of energy into the body so as to meet daily nutritional needs, which can increase student learning concentration. The purpose of this study was to determine the relationship between breakfast habits with nutritional status and student concentration at SDN Batu Tulis, Bogor district in 2022. Researchers used a quantitative method with a cross sectional study design and the type of sample in this study was non-probability sampling with total sampling technique. taken as many as 73 students. Collecting data for this study using a questionnaire with a questionnaire instrument breakfast habits, study concentration, and measuring BMI/U to measure nutritional status. This research uses univariate and bivariate analysis with Chi-Square test. The results showed that there was a significant relationship between breakfast habits and the nutritional status of students (p = 0.005) and OR = 0.220 (95% CI: 0.081 - 0.595) and there was a significant relationship between breakfast habits and student learning concentration (p = 0.009 ) and OR = 4,228 (95% CI: 1,535 - 11,647). Therefore, students are encouraged to eat breakfast before leaving for school so that their nutritional status and concentration in learning are safely controlled.